A novel homozygous CERS3 frameshift mutation causing autosomal recessive congenital ichthyosis type 9: A case report. - Almutlaq, Hamad; S. Aljuhani, Turki; Albayat , Methal; Ali N Aljalfan, Abdullah; Albreiki, Sarah (Acta Biomedica Atenei Parmensis, 2026)
Autosomal recessive congenital ichthyosis (ARCI) is a collection of uncommon keratinization disorders marked by widespread scaling and erythema from birth. CERS3 variants lead to ARCI type 9 (ARCI9) by interfering with ceramide biosynthesis and the formation of the epidermal barrier. We present a 25-year-old male, born as a collodion baby to consanguineous parents, who exhibited lifelong diffuse, plate-like scaling accompanied by mild ectropion. Histopathology revealed compact orthokeratosis accompanied by mild acanthosis. Genetic analysis identified a novel homozygous frameshift variant in CERS3 (NM_001292029.2:c.437del; p.[Ala146Valfs*9]), deemed likely pathogenic according to ACMG criteria. Parental carrier testing was recommended but has not yet been conducted. This case broadens the mutational spectrum of CERS3-related ichthyosis and underscores the necessity of amalgamating clinical, histological and molecular findings for accurate diagnosis. Genetic confirmation facilitates precise counselling, cascade testing and an enhanced comprehension of ceramide pathway deficiencies in ARCI.